Faktor-Faktor Pendorong dan Bentuk Perlindungan Hukum Terhadap Pegawai Koperasi Harian Korban Tindak Pidana Kekerasan Yang Dilakukan Konsumen Dalam Menjalankan Tugas Penagihan di Kota Kupang - Ketut Yugi Paulus M. Elliek; Rudepel Petrus Leo; Deddy R. Ch. Manafe (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Legal protection for daily cooperatives is very important to ensure that their duties are carried out fairly, in accordance with applicable regulations, and without violating the rights of cooperative members. However, in the implementation of this task, there are often unwanted situations, such as violent crimes that can threaten the safety and integrity of daily cooperative employees. The inability to pay debts can trigger emotions and frustration on the part of borrowers, which in turn can trigger acts of violence against daily cooperative employees in the city of Kupang. Based on the above background, the following problem formulation is proposed: (1) What are the factors that encourage the occurrence of acts of violence against cooperative employees when carrying out collection duties? (2) What is the form of legal protection provided by the government to cooperative employees when carrying out collection duties?. This research was carried out in Kupang City, precisely at the PNM Mekaar Office, Kelapa Lima Kupang Branch. This research is an empirical legal research, which is carried out with a legislative approach and a case approach. The data were analyzed in a descriptive-qualitative manner. Based on the results of the research conducted, it was obtained that: (1) factors that encourage acts of violence against cooperative employees when carrying out collection duties, including: (a) Internal factors, including; (a) morality and education, (b) low consumer income factors, (c) consumer economic pressure, (d) uncontrolled emotions, (e) the influence of alcohol. b) External factors, including; (a) risky environmental factors, (b) social factors. (2) Forms of legal protection provided by the government to cooperative employees when carrying out collection duties, including: (a) Preemptive protection: can mean taking preventive measures. (b) Preventive Protection: This protection involves various policies, regulations, and mechanisms. (c) Repressive protection: actions taken to address, stop, or punish unlawful acts. The author's advice is to report the incident of violence to your superior, cooperative management, or the authorities as soon as possible. Make sure to follow the cooperative's internal procedures related to complaints and handling of violence.